Renewable Energy, Subsidies, and the WTO: Where Has the Green Gone? - Patrice Bougette; Christophe Charlier (Fondazione Eni Enrico Mattei (FEEM), 2014)
Faced with the energy transition imperative, governments have to decide about public policy to promote renewable electrical energy production and to protect domestic power generation equipment industries. For example, the Canada Renewable energy dispute is over Feed-in tariff (FIT) programs in Ontario that have a local content requirement (LCR). The EU and Japan claimed that FIT programs constitutesubsidies that go against the SCM Agreement, and that the LCR is incompatible with the non-discrimination principle of the World Trade Organization (WTO). This paper investigates this issue using an international quality differentiated duopoly model in which power generation equipment producers compete on price. FIT programs including those with a LCR are compared for their impacts on trade, profits, amount of renewable electricity produced, and welfare. When quantities are taken into account, the results confirm discrimination. However, introducing a difference in the quality of the power generation equipment produced on both sides of the border provides more mitigated results. Finally, the results enable discussion of the question of whether environmental protection can be put forward as a reason for subsidizing renewable energy producers in light of the SCM Agreement.
Keywords: F18; L52; Q42; Q48; Q56; 330; Feed-in Tariffs; Subsidies; Local Content Requirement; Industrial Policy; Canada Renewable Energy Dispute; Trade Policy